FRAKTAL SEBAGAI SUMBER IDE PENGEMBANGAN DESAIN BATIK TUBAN - Puspa Wardani, Fernanda Rizky (Studi Budaya Nusantara, 2022)
The design for the pattern of Batik Tuban with Fractal visual idea was motivated by the availability of a chance to develop a new design that focuses on the visual processing of Fractals and Batik Tuban motif itself. The urge that generates this idea was taken not only because of the phenomena that Fractals are currently being explored, but also based on the unique characteristics of visual Fractals itself that can produce new various and diverse motifs. Visual Fractals are acquired from a software called "Ultra Fractal" which is then processed to be combined with Batik Tuban motif. This designing process produces a new pattern that associated with the typical motifs of the past towards today's textile products that is manufactured through digital processing techniques. The results of this design development can be concluded as: (1) From the visual Fractal idea, this design produces nine designs employing the original Batik Tuban motif as the main pattern which are classified into nine, they are three geometric designs, three flora designs and three fauna designs. (2) Three of the nine designs have been transformed into blouse fashion products using Japanese cotton which are polished by applying Batik Tulis techniques and dabbing them in the coloring process.